The role of entrepreneurial accompaniment bodies in establishing small and medium enterprises - Moulai, Amina (Finance and Business Economies Review, 2020)
The entrepreneurial orientation has become an imperative necessity through which many economic dilemmas can be resolved, especially the dependency on the hydrocarbons sector, unemployment, the high import bill and others, which requires the attention of the state to encourage the establishment and accompaniment of enterprises, and in this regard Algeria, like other countries, has created many bodies that It accompanies budding entrepreneurs, and through this study we seek to identify the extent of the youth’s desire to go towards contracting and establish their own institutions and the role that accompanying bodies play, especially in the nursery of small and medium-sized enterprises and the facility center, We carried out a field study that included a random sample consisting of 200 project holders in Wilayat El Bayadh, and we used in collecting data on a questionnaire designed for this purpose, then the data obtained was processed by using 20spss v and the study reached a set of results, the most important of which is that the activity of the accompaniment bodies is shrouded in a lot of The deficiency, mainly represented in the weakness of the processes of training the holders of project ideas, and if any, it is a standard formation that is not compatible with the requirements of the various projects The formation of employees in these bodies and their experience in the field and realities of the areas in which junior contractors are active do not qualify them for the accompanying process, the lack of databases necessary for local economic activities makes the process of market study, the economic feasibility of projects and the determination of the project needs difficult.